2017
DOI: 10.1093/carcin/bgx001
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet induced leptin and Wnt expression: RNA-sequencing and pathway analysis of mouse colonic tissue and tumors

Abstract: Obesity, an immense epidemic affecting approximately half a billion adults, has doubled in prevalence in the last several decades. Epidemiological data support that obesity, due to intake of a high-fat, western diet, increases the risk of colon cancer; however, the mechanisms underlying this risk remain unclear. Here, utilizing next generation RNA sequencing, we aimed to determine the high-fat diet (HFD) mediated expression profile in mouse colon and the azoxymethane/dextran sulfate sodium model of colon cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…Feeding the mice the WD perturbed the regeneration process, mainly in the ascending colon by reducing proliferation and expression of Wnt target genes. These findings were unexpected, as several studies reported the opposite [61,62]. Nevertheless, in a recent study in DSS-treated mice, reduced mucosal proliferation promoted the development of colonic dysplasia [63].…”
Section: Discussionmentioning
confidence: 86%
“…Feeding the mice the WD perturbed the regeneration process, mainly in the ascending colon by reducing proliferation and expression of Wnt target genes. These findings were unexpected, as several studies reported the opposite [61,62]. Nevertheless, in a recent study in DSS-treated mice, reduced mucosal proliferation promoted the development of colonic dysplasia [63].…”
Section: Discussionmentioning
confidence: 86%
“…The RNA-Seq study by Mangiola et al (2018) suggests that periprostatic adipose tissue from patients with high-risk prostate cancer has a distinct transcriptional signature, which was confirmed by qPCR in an expanded cohort. In particular, Leptin and Wnt have been demonstrated as the top two transcripts elevated in mouse high fat diet colon shared with tumors, using next generation RNA sequencing and pathway analysis (Penrose et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis, sequencing, differential expression testing, and pathway analysis were performed as described before [ 21 , 43 ]. Sequencing data for this study is available through NCBI's Sequence Read Archive (SRA) with accession number SRP093357.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted with QIAzol Lysis Reagent (Qiagen) followed by reverse transcription employing the SuperScript First-Strand Synthesis System (Thermo Fisher Scientific) and Oligo-dT12-18 primers according to the standard protocol [ 21 , 43 ]. The following primers were used for quantification of cDNA specifically binding FLRT3 (FLRT3-FOR 5′-GGTATTGCGGGTGCAAGATG-3′, FLRT3-REV 5′-GCCATCCCACGAACCTTTTC-3′), DGKI (DGKI- FOR 5′-CAGGTCTCGTACAGGAAAGCA-3′, DGKI REV-5′-ACTCCACTCCAAAGTCGCTC-3′), IFI16 (IFI16-FOR 5′-GAAGTGCCAGCGTAACTCCT-3′, IFI16-REV 5′-ACCTCAAACACCCCATTCACA-3′), and HPRT1 (HPRT1-FOR 5′-GACCAGTCAACAGGGGACAT-3′, HPRT1-REV 5′-AACACTTCGTGGGGTCCTTTTC-3′).…”
Section: Methodsmentioning
confidence: 99%